The development of a dynamically configured wireless ad-hoc multihop network protocol - Pretorius, Wynand (Stellenbosch : University of Stellenbosch, 2008)
Thesis (MScEng (Electrical and Electronic Engineering))--University of Stellenbosch, 2006.